2018
DOI: 10.1038/s42005-018-0082-8
|View full text |Cite
|
Sign up to set email alerts
|

Extremely reduced dielectric confinement in two-dimensional hybrid perovskites with large polar organics

Abstract: Two dimensional inorganic–organic hybrid perovskites (2D perovskites) suffer from not only quantum confinement, but also dielectric confinement, hindering their application perspective in devices involving the conversion of an optical input into current. In this report, we theoretically predict that an extremely low exciton binding energy can be achieved in 2D perovskites by using high dielectric-constant organic components. We demonstrate that in (HOCH2CH2NH3)2PbI4, whose organic material has a high dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
189
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(209 citation statements)
references
References 33 publications
20
189
0
Order By: Relevance
“…As ε barrier increases, the large dipole moment of 4FPEA cations essentially decreased the dielectric confinement effect, and thereby reduced the exciton binding energy. Recent publications also found that introducing the polar organic substituents substantially reduces the exciton binding energy of 2D perovskite films . The reduced exciton binding energy can also be reflected by the corresponding redshift of excitonic peaks and onset of the absorption edge of the 4FPEA‐based RPP film shown earlier.…”
Section: Summary Of Photovoltaic Parameters For the Devices With (Peamentioning
confidence: 74%
“…As ε barrier increases, the large dipole moment of 4FPEA cations essentially decreased the dielectric confinement effect, and thereby reduced the exciton binding energy. Recent publications also found that introducing the polar organic substituents substantially reduces the exciton binding energy of 2D perovskite films . The reduced exciton binding energy can also be reflected by the corresponding redshift of excitonic peaks and onset of the absorption edge of the 4FPEA‐based RPP film shown earlier.…”
Section: Summary Of Photovoltaic Parameters For the Devices With (Peamentioning
confidence: 74%
“…In present development of 2D and quasi‐2D perovskite solar cells, tuning the dielectric property of the organic cation spacer is becoming increasingly important to obtain highly efficient exciton dissociation and high mobility. Theoretically, it has been predicted that the dielectric confinement can be significantly suppressed by appropriately introducing an organic material ((HOCH 2 CH 2 NH 3 ) 2 PbI 4 ) with a relatively higher dielectric constant (≈37) into the 2D perovskite . It, as a consequence, leads to reduction of the binding energy for exciton dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Halide perovskites with the general formula of APbX 3 (A = MA, FA, and Cs; X = Cl, Br, and I) have been widely adopted in photovoltaics and lighting applications owing to their high absorption coefficient,12 intense photoluminescence (PL) emission,13 controllable optoelectronic property,14 and ability to grow by cost‐effective solution process 15. With elongated 1D structure and high refractive index compared with the environment, perovskite nanowires (NWs) and nanorods are able to emit strongly polarized light 16–19.…”
Section: Introductionmentioning
confidence: 99%